Optimal design of vortex chamber pump - Rogovyi, A.; Korohodskyi, V.; Khovanskyi, S.; Hrechka, I.; Medvediev, Y. (My University, 2021)
The difficult operating conditions during the pumping of abrasive solid mediums lead to the rapid wear of the mechanical parts of the pumps. The use of jet pumps can significantly increase the reliability and durability of pumping equipment. However, directflow jet pumps have low efficiency. The use of the centrifugal force led to the creation of new jet pumps - vortex chamber pumps. Their performance indicators are better than direct-flow jet pump ones. The geometric parameters of the flow channel of the vortex chamber pumps were optimized. The study was carried out experimentally and numerically. Numerical simulation is based on solving the RANS equations with the shear stress transport turbulence model. The geometrical dimensions of the vortex chamber pump with the best performance indicators such as pressure and flow are found. The maximum achievable operating parameters of the vortex chamber pump are analyzed. The comparison of simulation results with experimental data is made.
Keywords: vortex chamber pump; geometric parameters; technological processes